Implementation of Smoke-Free Zones in Schools in Indonesia - Eva Lyani Amelia; Nurhayati Adnan (Journal of Social Research, 2025)
Smoking is a global health problem that impacts not only active smokers but also on the people around them, especially children. In Indonesia, the prevalence of child smoking is increasing, so interventions such as the implementation of No Smoking Zones (KTR) in school environments are needed to prevent smoking behavior among students. To find out how the implementation of the No Smoking Area in the school environment in Indonesia. This study used the PRISMA method to conduct a literature review, with searches on the Scopus, Science Direct, Pubmed, and Google Scholar portals. The inclusion criteria include articles published between 2019-2024, focus on the school population in Indonesia, and are publicly accessible. Of the 144 articles found, 10 met the inclusion criteria and were further analyzed. The analysis shows that the implementation of KTR in schools in Indonesia varies. Although many schools have put up no-smoking signs and conducted socialization, there are still challenges such as lack of supervision, infirm sanctions, and the existence of smoking areas. The results showed that 66.2% of schools complied with the KTR, but many did not have an effective monitoring team. The implementation of KTR in schools has not been optimal. Continuous socialization, support from policymakers, and strict enforcement of sanctions are needed to improve compliance. With improvements in the implementation of KTR, it is hoped that it can reduce the prevalence of child smokers and create a healthier school environment.